Tiny houses and planning regulation for housing alternatives: the context of regional Victoria. Issue 3 (2nd October 2018) - Butt, Andrew; Stephenson, Carolyn
ABSTRACT: The emergence of 'Tiny Houses' as a dwelling and cultural phenomenon reveals significant frictions with regulatory systems orientated towards orthodox housing models. In this regard the tiny house movement shares a genealogy with traditions of self-build housing and more recent sustainable and affordable housing alternatives. In each instance, regulatory frameworks have created points of resistance, including a planning system that differentiates between various categories of permanent and temporary accommodation. In regional areas such tensions are apparent in various forms; fluidity between temporary and permanent residential uses, unregulated self-building and the use of non-residential structures for housing. We position Tiny Houses as a category of these conflicts, arguing that the regulatory intent of restricting dwellings has a range of purposes in Victorian planning law, including the protection of farmland, the regulation of wastewater and the maintenance of housing standards. This paper will utilise Victorian planning decisions and definitions to consider the way in which non-conforming housing models have been addressed in rural settings and credibility given to claims of sustainability and innovation in housing provision within the broader decision-making framework. The results suggest that varied housing is enabled by the planning system, however category issues remain regarding mobility, permanence and impact.